Prospects of green economy as a new paradigm of development - A. A. Pakina; V. A. Gorbanyov (Vestnik MGIMO-Universiteta)
Transition of the world development to the post-industrial phase is accompanied by the global challenges, which could be solved within the "green economy". The basic principles of a "green economy" (GE) correspond to the concepts of balanced development and of rational nature use: the "green economy's" concept focuses on the idea of living standards improvement and economic growth while reducing the environmental damage. The indicators of GE reflect the complexity of the integrated assessment of economic, environmental and social outcomes. Since the common approach to such assessment has not yet been adopted, the development of global and national economies is often compared with the dynamics of their energy or resource intensity. This approach allows to take into account the "life cycle" of products and to allocate the responsibility of countries for environmental damage. Foreign experience can be used to implement the ideas of GE in Russia and CIS countries. Most experts are sceptical about these prospects due to its dependence on fossil fuels. Nevertheless, the experience of some regions of Russia and Kazakhstan shows the viability of strategies based on the renewable energy sources. Elaboration of financing mechanisms for "green" development is equally important. Such mechanisms must be adapted to meet the environmental needs of society, with attention to the losses from natural disasters and environmental damage. Today, national environmental management strategies are based on the transition to a resource-efficient low-carbon economy, and contribute a lot to the search for opportunities for the practical implementation of this concept.